88. Intraoperative motor evoked potentials monitoring: Assessment of corticospinal tract development in very young children. Issue 4 (April 2016) - Lanteri, P.; Prato, G.; Piatelli, G.; Martelli, S.; Tumolo, M.; Andaloro, A.; Veneselli, E.; Cama, A.
Abstract : The most frequent method of intraoperative motor tract monitoring now in widespread use is referred to as transcranial electric stimulation (TES) applied to the motor cortex recordings of reliable muscle motor evoked responses (MEPs). While monitoring of MEPs is well established in adults, its use and reliability in the pediatric population are debated. Overall, TES is considered a safe method. Between November 2013, and February 2015, at G. Gaslini Institute we performed 100 procedures (80 neurosurgical and 20 scoliosis procedures) (age range, 1 month and 20 days to 20 yr) with intraoperative motor tract monitoring. 14 of the surgeries were performed in children who were younger than 1 year of age. TES was performed to record MEP from abductor brevis pollicis, tibialis anterior (TA) and/or abductor hallucis muscles. The standard anesthesia regimen consisted of propofol, and remifentanil. There were no complications related to this technique. There was an exponential, systematic reduction in the latency of MEP with age, especially for lower limb within 3 months of age, less noticeable until one year of age. The adult-type response was present by 2 years. The most significant maturation of corticospinal tract responses to TES takes place during the first 3 months of life.